Kerahasiaan Bank vs Hak Atas Informasi: Mengurai Konflik Kepentingan dalam Perlindungan Data Pribadi - Widiya Dwi Novarianti; Athalia Pranata Putri S Meliala; Nova Arini Stevia Yusuf; Bintang Naharika Citra Melati (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Bank confidentiality and the right to information are two principles that often have the potential to conflict, especially in the context of personal data protection. Bank have an obligation to maintain the confidentiality of customer data in accordance with the principles of bank secrecy regulated in the banking law, but on the other hand, they are also required to provide information to the authorities based on certain statutory regulations, such as tax law, anti money laundering and eradication. Terrorism. This conflict creates challenges in ensuring the protection of customers personal data without violating the public's right to information. In the context of Indonesian law, regulations regarding through harmonization of regulations which prioritize the principles of proportionality and public interest. This research outlines the efforts that banks can make to maintain a balance between these two obligations, including the implementation of data security technology, internal supervision, and compliance with the relevant legal framework. This strategy is expected while fulfilling banking legal obligations.